2010
DOI: 10.1038/ajg.2009.713
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Endoscopy Has a Significantly Higher Diagnostic Yield in Patients With Suspected and Established Small-Bowel Crohn's Disease: A Meta-Analysis

Abstract: Our meta-analysis demonstrates that CE is superior to SBR, CTE, and C+IL in the evaluation of suspected CD patients. CE is also a more effective diagnostic tool in established CD patients compared with SBR, CTE, and PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
230
2
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(246 citation statements)
references
References 23 publications
5
230
2
9
Order By: Relevance
“…Correspondence to: A. Rychlik, e-mail: rychlik@uwm.edu.pl endoscopic techniques, despite recent advances in this field, are characterized by a narrow range of practical applications, in particular in examinations of the ileum, and require anesthesia (Dionisio et al 2010, Gibbs and Bloomfeld 2012, Sarria et al 2013. Capsule endoscopy is a non-invasive method for macroscopic evaluations of the mucosa covering the small and large intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondence to: A. Rychlik, e-mail: rychlik@uwm.edu.pl endoscopic techniques, despite recent advances in this field, are characterized by a narrow range of practical applications, in particular in examinations of the ileum, and require anesthesia (Dionisio et al 2010, Gibbs and Bloomfeld 2012, Sarria et al 2013. Capsule endoscopy is a non-invasive method for macroscopic evaluations of the mucosa covering the small and large intestine.…”
Section: Introductionmentioning
confidence: 99%
“…The difference of the diagnostic yield between CE and MR enterography was not statistically significant. Therefore, CE had a significantly higher yield of diagnosis compared with most of other modalities for small-bowel CD [17]. Indications for performing CE in pediatric patients are known and suspected IBD, occult GI bleeding, survey of known polyposis syndrome, persistent vomiting and abdominal pain, and posttransplantation lymphoproliferative disease.…”
Section: The Application Of Ce To Eva-luate Small-bowel CDmentioning
confidence: 99%
“…A previous study demonstrated that CE is superior to small-bowel radiography, computed tomography enterography (CTE), and colonoscopy with ileoscopy in the evaluation of adult patients with suspected CD (Dionisio, 2010). As well as adult patients, CE is more sensitive than radiological and standard endoscopic modalities in the detection of small bowel CD distribution, OGIB source, and presence of polyps in children (Thomson, 2007;Guilhon de Araujo Sant'Anna, 2005).…”
Section: Comparison With Other Modalitiesmentioning
confidence: 99%